Structural dynamics, volume 3 proceedings of the 28th IMAC, a conference on structural dynamics, 2010 - Proulx, Thomas A. (Conference proceedings of the society for experimental mechanics series, 2011)
This the third volume of five from the 28th IMAC on Structural Dynamics and Renewable Energy, 2010 brings together 146 chapters on Structural Dynamics. It presents early findings from experimental and computational investigations of on a wide range of area within Structural Dynamics, including studies such as Simulation and Validation of ODS Measurements made Using a Continuous SLDV Method on a Beam Excited by a Pseudo Random Signal, Comparison of Image Based, Laser, and Accelerometer Measurements, Modal Parameter Estimation Using Acoustic Modal Analysis, Mitigation of Vortex-induced Vibrations in Long-span Bridges, and Vibration and Acoustic Analysis of Brake Pads for Quality Control.